2009
DOI: 10.4319/lo.2009.54.4.1060
|View full text |Cite
|
Sign up to set email alerts
|

Benthic community structure and spatiotemporal thermal regimes in two upwelling ecosystems: Comparisons between South Africa and Chile

Abstract: On the basis of 16-yr satellite time series (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) of sea surface temperature (SST) and using univariate and multivariate statistical techniques, we quantified patterns of fluctuation in oceanographic conditions, as well as their spatial structure along the coasts of South Africa and Chile between 29.0u and 34.5uS. Since variations in environmental conditions over multiple timescales are driven by oceanographic-atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…Thinly filamentous and single-layer foliose algae, characterized by high mass-specific productivity (Littler and Littler, 1980;Nielsen and Sand-Jensen, 1990;Steneck and Dethier, 1994) and the ability to rapidly colonize bare spaces at mid to upper intertidal levels (Littler and Littler, 1980;Lubchenco and Gaines, 1981), are a seasonal to semi-permanent component of rocky shore communities along most of the temperate regions of the world (Hawkins and Hartnoll, 1983a;Jenkins et al, 2008;Poore et al, 2012;Wieters et al, 2009). These algal groups are collectively known as 'ephemerals' because they build up dense patches that develop rapidly, and frequently collapse within a few months.…”
Section: Introductionmentioning
confidence: 99%
“…Thinly filamentous and single-layer foliose algae, characterized by high mass-specific productivity (Littler and Littler, 1980;Nielsen and Sand-Jensen, 1990;Steneck and Dethier, 1994) and the ability to rapidly colonize bare spaces at mid to upper intertidal levels (Littler and Littler, 1980;Lubchenco and Gaines, 1981), are a seasonal to semi-permanent component of rocky shore communities along most of the temperate regions of the world (Hawkins and Hartnoll, 1983a;Jenkins et al, 2008;Poore et al, 2012;Wieters et al, 2009). These algal groups are collectively known as 'ephemerals' because they build up dense patches that develop rapidly, and frequently collapse within a few months.…”
Section: Introductionmentioning
confidence: 99%
“…We categorized species into one of 8 (benthic) or 5 (fish) functional groups based on a) morphological and anatomical traits related to maximum possible rate of biomass production (mass-specific growth; ability to quickly assimilate nutrient availability) and resistance to herbivory [algae; largely following Steneck & Dethier (1994) with grouping modifications similar to Broitman et al (2001) and Wieters et al (2009) Randall & Cea (2011)]. Benthic: 1) ephemeral algae, 2) corticated algae, 3) leathery algae, 4) crustose algae, 5) corals, 6) filter feeders, 7) herbivores, and 8) predators.…”
Section: Fish Surveysmentioning
confidence: 99%
“…and spatial cover of sessile species (e.g., corals, macroalgae, sponges, barnacles, etc.) at shallow (<8 m), mid (10-15 m), and deep (17-23 m) zones were quantified at 2-3 rocky reefs using the standard transect-quadrat method, as described in detail in Wieters et al (2009). A minimum of ten 0.25 m graphed.…”
Section: Benthic Surveysmentioning
confidence: 99%
“…The third aspect is temperature variation, one of the most important factors for the regulation of biological processes in ectothermic organisms (KORDAS et al, 2011). Therefore, these aspects may play an important role in the successional process of benthic communities (MCCOOK; CHAPMAN, 1997;MENGE et al, 2004;WIETERS et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies on the interface between benthic ecology and oceanography have identified a number of the major coastal phenomena that can control or shape the organization of benthic communities (reviewed by WIETERS et al, 2009). Coastal upwelling is one of these phenomena, and it occurs when deep, cold and nutrient-rich waters reach the surface near the coast (VALENTIN, 1987).…”
Section: Introductionmentioning
confidence: 99%